2020
DOI: 10.3390/app10113820
|View full text |Cite
|
Sign up to set email alerts
|

A Household Energy Efficiency Index Assessment Method Based on Non-Intrusive Load Monitoring Data

Abstract: Various countries in the world are vigorously developing energy-saving industries and attaching importance to the improvement of household energy efficiency, but it is difficult to evaluate user power consumption characteristics due to insufficient information and large data granularity. It is, however, possible to evaluate the energy efficiency of household users via non-intrusive load monitoring (NILM). This paper explores the energy efficiency assessment of residential users and proposes a household energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The objective is to optimize energy use, reduce waste, and achieve a more sustainable and cost-effective operation. In recent years, methods for energy efficiency assessment based on NILM have been developed [287], [293]- [295]. These studies have demonstrated that by combining the analysis results of energy efficiency indicators, household users can identify weaknesses in their energy efficiency and improve overall electricity efficiency by adjusting their energy-use patterns.…”
Section: ) User Behavior Understandingmentioning
confidence: 99%
“…The objective is to optimize energy use, reduce waste, and achieve a more sustainable and cost-effective operation. In recent years, methods for energy efficiency assessment based on NILM have been developed [287], [293]- [295]. These studies have demonstrated that by combining the analysis results of energy efficiency indicators, household users can identify weaknesses in their energy efficiency and improve overall electricity efficiency by adjusting their energy-use patterns.…”
Section: ) User Behavior Understandingmentioning
confidence: 99%
“…Non-invasive load monitoring (NILM) technologies have been employed to collect more detailed data on the utilisation of certain appliances [125,126]. Data collection capabilities of the Internet of Things (IoT) technology have been significantly improved in recent research.…”
Section: Data and Measurement Techniques For The Prediction Of Electr...mentioning
confidence: 99%
“…The disaggregated information of home appliances obtained by NILM is a great tool to help in the evaluation of the EE in buildings. In [47], a NILM-based assessment method is proposed to evaluate the EE of households. To enhance the accuracy, this study introduced an EE assessment index of residents using the analysis of both electrical and non-electrical factors that could affect energy efficiency.…”
Section: Energy Efficiency Assessment Of Hvacs Using Nilmmentioning
confidence: 99%